RESULT OF STUDYING SOME ACUTE PHASE PROTEINS AND CORTISOL IN PREGNANT EWES - A., Ulaankhuu; G., Lkhamjav; Nakamura, Yoshio; M., Zolzaya (Mongolian Journal of Agricultural Sciences, 2017)
One of the specific characteristics of Mongolian livestock is that parturition occurs during the cold winter and spring seasons. Aim of our study is to investigate acute phase proteins (APP) in pregnant ewes during the time of cold temperature stress. According to the study, haptoglobin (Hp) concentration in serum of pregnant ewes was highest in February, as well as high variation of Hp was detected during the remaining months. In addition, alpha -1 acid glycoprotein (α1AGР) was also highest in February, but decreased gradually in the following months.